Malnutrition Predicts Infectious and Wound Complications Following Posterior Lumbar Spinal Fusion. Issue 21 (1st November 2016) - Bohl, Daniel D.; Shen, Mary R.; Mayo, Benjamin C.; Massel, Dustin H.; Long, William W.; Modi, Krishna D.; Basques, Bryce A.; Singh, Kern
Abstract : Study Design: A retrospective review of data collected prospectively by the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP). Objective: The aim of this study was to investigate the association between preoperative hypoalbuminemia, a marker for malnutrition, and complications during the 30 days following posterior lumbar fusion surgery. Summary of Background Data: Malnutrition is a potentially modifiable risk factor that may contribute to complications following spinal surgery. Although prior studies have identified associations between malnutrition, delayed wound healing, and surgical site infection (SSI), the evidence for such a relationship within spine surgery is mixed. Methods: Patients who underwent posterior lumbar spinal fusion of one to three levels as part of the ACS-NSQIP were identified. Patients without preoperative serum albumin concentration were excluded. Outcomes were compared between patients with and without hypoalbuminemia (defined as serum albumin concentration <3.5 g/dL). All comparisons were adjusted for baseline differences between populations. Results: Four thousand three hundred ten patients were included. The prevalence of hypoalbuminemia was 4.8%. In comparison to patients with normal albumin concentration, patients with hypoalbuminemia had a higher risk for occurrence of wound dehiscence [1.5% vs . 0.2%, adjusted relative risk (RR) = 5.8, P  = 0.006], SSI (5.4% vs . 1.7%, adjusted RR = 2.3, P  = 0.010), and urinary tract infection (5.4% vs . 1.5%, adjusted RR = 2.5, P  = 0.005). Similarly, patients with hypoalbuminemia had a higher risk for unplanned hospital readmission within 30 days of surgery (11.7% vs . 5.4%, RR = 1.8, P  < 0.001). Finally, patients with hypoalbuminemia had a longer mean inpatient stay (5.2 vs . 3.7 days, RR = 1.2, P  < 0.001). Conclusion: The present study suggests that malnutrition is an independent risk factor for infectious and wound complications following posterior lumbar fusion. Malnutrition was also associated with an increased length of stay and readmission. Future studies should evaluate methods of correcting malnutrition before lumbar spinal surgery. Such efforts have the potential to meaningfully decrease the rates of adverse events following this procedure. Level of Evidence: 3